A CEL study of dynamic slamming response and failure mechanism on corrugated core composite-metal sandwich structures. (3rd June 2022) - Wang, Changzi; Cao, Shihui; Lu, Shaojia; Hu, Zhiqiang; Yao, Lu; He, Wentao
ABSTRACT: This paper aims to evaluate the dynamic response and failure mechanism of corrugated core composite metal sandwich structures under the complicated fluid-structure interaction. Firstly, a reliable numerical model is established in ABAQUS/Explicit using Coupled Eulerian-Lagrangian (CEL) method. Subsequently, the influence of slamming velocity and aluminum core direction on dynamic response is studied in virtue of hydrodynamic force, deflection, transient pressure and microstrain. Finally, the damage modes and failure mechanism are studied by the ultimate damage modes exploration and progressive damage analysis. Results illustrate that hydrodynamic force experiences a sudden ascending stage before reaching the peak value, which is sensitive to the variation of local deadrise angle near the chine. Severe core skin debonding and aluminum core buckling near the chine are both alleviated under 10 m/s compared with that under 8 m/s for transverse core sandwich structures, accompanied with dominating matrix tension damage face sheet.